CK19 and OV6 Expressions in the Liver of 2-AAF/CCl4 Rat Model - Arwinda, Romy; Liem, Isabella Kurnia; Fatril, Ayu Eka; Oktorina, Fanny; Husna, Firda Asma’ul; Kodariah, Ria; Wuyung, Puspita Eka (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Liver regeneration on a chronic liver injury with rat model research is urgent to study the pathology of human chronic diseases. 2-Acetylaminofluorene (2-AAF) and Carbon Tetrachloride (CCl4) can be applied to study about liver regeneration by liver stem cells, known as oval cells. The use of 2-AAF and CCl4 (2-AAF/CCl4) to induce chronic liver injury can lead severe hepatocyte damages and extensive fibrosis. AIM: to observed the OV6 and CK19 expression in the liver of 2AAF/CCl4 rat model. METHODS: In this research, a high dose of 2-AAF (10mg/kg) was applied and combined repeatedly with CCl4 (2ml/kg) for 12 weeks. An immunohistochemistry (IHC) procedure by using OV6 and CK19 antibodies was also applied to examine the regeneration of oval cells. Both antibodies expressions were then examined semi-quantitatively according to the expressions percentage of each sample based on the liver zone. We have observed the OV6 and CK19 expressions in every zone, including in portae hepatis area. RESULTS: The results showed that OV6 and CK19 with the highest expression in the zone I. A significant difference between OV6 and CK19 expressions was revealed in healthy (control group) and 2-AAF/CCl4 groups (both indicating p=0.045). Moreover, a ductular reaction was also found in Zone I and II of the 2-AAF/CCl4. CONCLUSIONS: We conclude that 2-AAF/CCl4 induced chronic rat liver injury model, could be utilized to investigate the oval cells with OV6 and CK19 expression.